2015
DOI: 10.1103/physrevb.92.075439
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructures of transition metal dichalcogenides

Abstract: The structural, electronic, optical, and photocatalytic properties of out-of-plane and in-plane heterostructures of transition metal dichalcogenides are investigated by (hybrid) first principles calculations. The out-of-plane heterostructures are found to be indirect band gap semiconductors with type-II band alignment. Direct band gaps can be achieved by moderate tensile strain in specific cases. The excitonic peaks show blueshifts as compared to the parent monolayer systems, whereas redshifts occur when the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
127
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(135 citation statements)
references
References 49 publications
(62 reference statements)
5
127
0
3
Order By: Relevance
“…Also, the different structures of vertical and in‐plane heterostructures make their properties diverse. Amin et al theoretically reported that vertical and in‐plane MoS 2 –WS 2 , MoSe 2 –WSe 2 , and MoTe 2 –WTe 2 heterostructures exhibit obvious different electronic and optical properties . As for the electronic properties, all three vertical heterostructures have indirect bandgaps.…”
Section: D Tmd Heterostructuresmentioning
confidence: 99%
“…Also, the different structures of vertical and in‐plane heterostructures make their properties diverse. Amin et al theoretically reported that vertical and in‐plane MoS 2 –WS 2 , MoSe 2 –WSe 2 , and MoTe 2 –WTe 2 heterostructures exhibit obvious different electronic and optical properties . As for the electronic properties, all three vertical heterostructures have indirect bandgaps.…”
Section: D Tmd Heterostructuresmentioning
confidence: 99%
“…[9][10][11][12][13] Although antimonene has not been experimentally verified up to now, there are many intriguing properties, obtainable through ab initio simulations, which require the attention of scientific community. The rise in interest of antimonene in photonics and optoelectronics is supported by the numerous applications of similar monolayer materials ranging from solar cells and light-emitting devices to touch screens, photodetectors and ultrafast lasers.…”
Section: A Introductionmentioning
confidence: 99%
“…26 The EA of 2-propanol is unknown to the best of our knowledge, so we used that of isopropyl radical for calculating the electronegativity. 25 The electronegativity of TMDC (χ TMDC ) can be expressed as: 29,30 …”
mentioning
confidence: 99%